Dynamic nanoindentation by instrumented nanoindentation and force microscopy: a comparative review - Cohen, Sidney R.; Kalfon-Cohen, Estelle (Beilstein Journal of Nanotechnology, 2013)
Viscoelasticity is a complex yet important phenomenon that drives material response at different scales of time and space. Burgeoning interest in nanoscale dynamic material mechanics has driven, and been driven by two key techniques: instrumented nanoindentation and atomic force microscopy. This review provides an overview of fundamental principles in nanoindentation, and compares and contrasts these two techniques as they are used for characterization of viscoelastic processes at the nanoscale.
Keywords: atomic force microscopy; loss modulus; nanoindentation; storage modulus; viscoelasticity

(untitled) - Ashkin, A.; Dziedzic, J. M.; Bjorkholm, J. E.; Chu, S. (Opt. Lett., 1986)

(untitled) - Tabor, D.; Winterton, R. H. S. (Proc. R. Soc. London, Ser. A, 1969)

(untitled) - Israelachvili, J. N.; Tabor, D. (Proc. R. Soc. London, Ser. A, 1972)

Atomic Force Microscopy Based Nanorobotics - Xie, H.; Onal, C.; Régnier, S.; Sitti, M. (Springer-Verlag, 2012)

(untitled) - Zhou, J.; Komvopoulos, K. (J. Appl. Phys., 2006)

Applications des Potentiels a I'etude de equilibre et du mouvement des solides elastiques - Boussinesq, J. (Gauthier-Villars, 1885)

(untitled) - Hertz, H. (J. Reine Angew. Math., 1882)

(untitled) - Sneddon, I. N. (Int. J. Eng. Sci. (Oxford, U. K.), 1965)

Contact Mechanics - Johnson, K. L. (Cambridge Univ. Press, 1985)

(untitled) - Tabor, D. (J. Colloid Interface Sci., 1977)

(untitled) - Derjaguin, B. V.; Muller, V. M.; Toporov, Yu. P. (J. Colloid Interface Sci., 1975)

(untitled) - Johnson, K. L.; Kendall, K.; Roberts, A. D. (Proc. R. Soc. London, Ser. A, 1971)

(untitled) - Barthel, E. (J. Colloid Interface Sci., 1998)

(untitled) - Maugis, D.; Barquins, M. (J. Phys. D, 1978)

(untitled) - Schwarz, U. D. (J. Colloid Interface Sci., 2003)

(untitled) - Bulychev, S. I.; Alekhin, V. P.; Shorshorov, M. K.; Ternovskii, A. P.; Shnyrev, G. D. (Zavod. Lab., 1975)

(untitled) - Ternovskii, A. P.; Alekhin, V. P.; Shorshorov, M. K.; Khrushchov, M. M.; Skvortsov, V. N. (Zavod. Lab., 1974)

(untitled) - Loubet, J. L.; Georges, J. M.; Marchesini, O.; Meille, G. (J. Tribol., 1984)

(untitled) - Pethica, J. B.; Hutchings, R.; Oliver, W. C. (Philos. Mag. A, 1983)

(untitled) - Pethica, J. B.; Oliver, W. C. (Phys. Scr., 1987)

(untitled) - Binning, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Doerner, M. F.; Nix, W. D. (J. Mater. Res., 1986)

(untitled) - Oliver, W. C.; Pharr, G. M. (J. Mater. Res., 1992)

(untitled) - Oliver, W. C.; Pharr, G. M. (J. Mater. Res., 2004)

(untitled) - Pharr, G. M.; Oliver, W. C.; Brotzen, F. R. (J. Mater. Res., 1992)

(untitled) - Miyake, K.; Fujisawa, S.; Korenaga, A.; Ishida, T.; Sasaki, S. (Jpn. J. Appl. Phys., 2004)

(untitled) - Beegan, D.; Chowdhury, S.; Laugier, M. T. (Surf. Coat. Technol., 2005)

(untitled) - Poole, W. J.; Ashby, M. F.; Fleck, N. A. (Scr. Mater., 1996)

(untitled) - Overney, R. M.; Leta, D. P.; Pictroski, C. F.; Rafailovich, M. H.; Liu, Y.; Quinn, J.; Sokolov, J.; Eisenberg, A.; Overney, G. (Phys. Rev. Lett., 1996)

(untitled) - Vanlandingham, M. R.; McKnight, S. H.; Palmese, G. R.; Eduljee, R. F.; Gillespie, J. W., Jr; McCulough, R. L. (J. Mater. Sci. Lett., 1997)

Interfacial Properties on the Submicron Scale - Asif, S. A.; Colton, R. J.; Wahl, K. J. (Nanoscale Surface Mechanical Property Measurements: Force Modulation Techniques Applied to Nanoindentation, 2000)

(untitled) - Odegard, G. M.; Gates, T. S.; Herring, T. M. (Exp. Mech., 2005)

(untitled) - Greenwood, J. A.; Johnson, K. L. (J. Colloid Interface Sci., 2006)

(untitled) - Han, L.; Frank, E. H.; Greene, J. J.; Lee, H.-Y.; Hung, H.-H. K.; Grodzinsky, A. J.; Ortiz, C. (Biophys. J., 2011)

(untitled) - vanLandingham, M. R.; Chang, N.-K.; Drzal, P. L.; White, C. C.; Chang, S.-H. (J. Polym. Sci., Part B: Polym. Phys., 2005)

(untitled) - Gao, H.; Chiu, C.-H.; Lee, J. (Int. J. Solids Struct., 1992)

(untitled) - Hay, J.; Crawford, B. (J. Mater. Res., 2011)

(untitled) - Chen, X.; Vlassak, J. J. (J. Mater. Res., 2001)

(untitled) - Xu, H.; Pharr, G. M. (Scr. Mater., 2006)

(untitled) - Ebenstein, D. M.; Wahl, K. J. (J. Colloid Interface Sci., 2006)

(untitled) - Notbohm, J.; Poon, B.; Ravichandran, G. (J. Mater. Res., 2011)

(untitled) - Cohen, S. R. (Heterog. Chem. Rev., 1994)

(untitled) - Aimé, J. P.; Elkaakour, Z.; Gauthier, S.; Michel, D.; Bouhacina, T.; Curély, J. (Surf. Sci., 1995)

(untitled) - Liu, Y.; Wu, T.; Evans, D. F. (Langmuir, 1994)

(untitled) - Bhushan, B.; Koinkar, V. N. (Appl. Phys. Lett., 1994)

(untitled) - Withers, J. R.; Aston, D. E. (Adv. Colloid Interface Sci., 2006)

(untitled) - Cohen, S. R.; Apter, N.; Jesse, S.; Kalinin, S.; Barlam, D.; Peretz, A. I.; Ziskind, D.; Wagner, H. D. (Isr. J. Chem., 2008)

(untitled) - Unertl, W. N. (J. Vac. Sci. Technol., A, 1999)

(untitled) - VanLandingham, M. R. (J. Res. Natl. Inst. Stand. Technol., 2003)

(untitled) - VanLandingham, M. R.; Villarrubia, J. S.; Guthrie, W. F.; Meyers, G. F. (Macromol. Symp., 2001)

(untitled) - Butt, H.-J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

(untitled) - Briscoe, B. J.; Fiori, L.; Pelillo, E. (J. Phys. D: Appl. Phys., 1998)

(untitled) - Feng, G.; Ngan, A. H. W. (J. Mater. Res., 2002)

(untitled) - Korobko, R.; Kim, S. K.; Kim, S.; Cohen, S. R.; Wachtel, E.; Lubomirsky, I. (Adv. Funct. Mater., 2013)

(untitled) - Moeller, G. (J. Polym. Sci., Part B: Polym. Phys., 2009)

(untitled) - Jakes, J. J.; Lakes, R. S.; Stone, D. S. (J. Mater. Res., 2012)

(untitled) - Attard, P. (Phys. Rev. E, 2001)

(untitled) - Attard, P. (Langmuir, 2001)

(untitled) - Oyen, M. L.; Cook, R. F. (J. Mech. Behav. Biomed. Mater., 2009)

Visoelastic properties of Polymers - Ferry, J. D. (Wiley, 1980)

Introduction fo Polymer Viscoelasticity - Shaw, M. T.; MacKnight, W. J. (John Wiley & Sons, 2005)

(untitled) - Wahl, K. J.; Asif, S. A. S.; Greenwood, J. A.; Johnson, K. L. (J. Colloid Interface Sci., 2006)

(untitled) - Burnham, N. A.; Gremaud, G.; Kulik, A. J.; Gallo, P.-J.; Oulevey, F. (J. Vac. Sci. Technol., B, 1996)

(untitled) - Herbert, E. G.; Oliver, W. C.; Pharr, G. M. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Vandamme, M.; Ulm, F.-J. (Int. J. Sol. Struct., 2006)

Introduction to Physical Polymer Science - Sperling, L. H. (Wiley, Hoboken, 2005)

(untitled) - Chakravartula, A.; Komvopoulos, K. (Appl. Phys. Lett., 2006)

(untitled) - Cappella, B.; Kaliappan, S. K.; Sturm, H. (Macromolecules, 2005)

(untitled) - Loubet, J. L.; Oliver, W. C.; Lucas, B. N. (J. Mater. Res., 2000)

(untitled) - Williams, M. L.; Landel, R. F.; Ferry, J. D. (J. Am. Chem. Soc., 1955)

(untitled) - Sakharova, N. A.; Fernandes, J. V.; Antunes, J. M.; Oliveira, M. C. (Int. J. Solids Struct., 2009)

Mater. Res. Soc. Symp. Proc. - Lucas, B. N.; Oliver, W. C.; Swindeman, J. E. (1998)

(untitled) - Asif, S. A. S.; Wahl, K. J.; Colton, R. J. (Rev. Sci. Instrum., 1999)

(untitled) - Herbert, E. G.; Oliver, W. C.; Lumsdaine, A.; Pharr, G. M. (J. Mater. Res., 2009)

(untitled) - White, C. C.; VanLandingham, M. R.; Drzal, P. L.; Chang, N. K.; Chang, S.-H. (J. Polym. Sci., Part B: Polym. Phys., 2005)

(untitled) - Tranchida, D.; Kiflie, Z.; Acierno, S.; Piccarolo, S. (Meas. Sci. Technol., 2009)

(untitled) - Tsukruk, V. V.; Gorbunov, V. V.; Huang, Z.; Chizhik, S. A. (Polym. Int., 2000)

(untitled) - Huang, G.; Wang, B.; Lu, H. (Mech. Time-Depend. Mater., 2004)

(untitled) - Yang, S.; Zhang, Y.-W.; Zeng, K. (J. Appl. Phys., 2004)

(untitled) - Sun, Y.; Walker, G. C. (Langmuir, 2005)

(untitled) - Gannepalli, A.; Yablon, D. G.; Tsou, A. H.; Proksch, R. (Nanotechnology, 2011)

(untitled) - Garcia, R.; Herruzo, D. T. (Nat. Nanotechnol., 2012)

(untitled) - Tirosh, E.; Benassi, E.; Pipolo, S.; Mayor, M.; Valášek, M.; Frydman, V.; Corni, S.; Cohen, S. R. (Beilstein J. Nanotechnol., 2011)

(untitled) - Medalsy, I. D.; Müller, D. J. (ACS Nano, 2013)

(untitled) - Gotsmann, B.; Seidel, C.; Anczykowski, B.; Fuchs, H. (Phys. Rev. B, 1999)

(untitled) - Stark, M.; Stark, R. W.; Heckl, W. M.; Guckenberger, R. (Proc. Natl. Acad. Sci. U. S. A., 2002)

Applied Scanning Probe Methods Vol II - Rabe, U. (Atomic Force Acoustic Microscopy, 2006)

(untitled) - Sahin, O.; Magonov, S.; Su, C.; Quate, C. F.; Solgaard, O. (Nat. Nanotechnol., 2007)

(untitled) - Guo, S.; Solares, S. D.; Mochalin, V.; Neitzel, I.; Gogotsi, Y.; Kalinin, S. V.; Jesse, S. (Small, 2012)

(untitled) - Jesse, S.; Kalinin, S. V.; Proksch, R.; Baddorf, A. P.; Rodriguez, B. J. (Nanotechnology, 2007)

(untitled) - Welker, J.; Illek, E.; Giessibl, R. J. (Beilstein J. Nanotechnol., 2012)

(untitled) - Cleveland, J. P.; Anczykowski, B.; Schmid, A. E.; Elings, V. B. (Appl. Phys. Lett., 1998)

(untitled) - Scott, W. W.; Bhushan, B. (Ultramicroscopy, 2003)

Amplitude Modulation Atomic Force Microscopy - Garcia, R. (Wiley-VCH Verlag GmbH & Co. KgaA, 2010)

(untitled) - Friedenberg, M. C.; Mate, M. C. (Langmuir, 1996)

(untitled) - Garcia, R.; Gómez, C. J.; Martinez, N. F.; Patil, S.; Dietz, C.; Magerle, R. (Phys. Rev. Lett., 2006)

(untitled) - Eastman, T.; Zhu, D.-M. (Langmuir, 1996)

(untitled) - Xu, X.; Koslowski, M.; Raman, A. (J. Appl. Phys., 2012)

(untitled) - Radmacher, M.; Tillmann, R. W.; Gaub, H. E. (Biophys. J., 1993)

(untitled) - Yang, N.; Wong, K. K. H.; de Bruyn, J. R.; Hutter, J. L. (Meas. Sci. Technol., 2009)

(untitled) - McGuiggan, P. M.; Yarusso, D. J. (J. Mater. Res., 2004)

(untitled) - Minary-Jolanadan, M.; Yu, M. F. (Ultramicroscopy, 2008)

(untitled) - Yuya, P. A.; Hurley, D. C.; Turner, J. A. (J. Appl. Phys., 2008)

(untitled) - Mahaffy, R. E.; Park, S.; Gerde, E.; Käs, J.; Shih, C. K. (Biophys. J., 2004)

(untitled) - Smith, B. A.; Tolloczko, B.; Martin, J. G.; Grütter, P. (Biophys. J., 2005)

(untitled) - Lange, M.; van Vörden, D.; Möller, R. (Beilstein J. Nanotechnol., 2012)

(untitled) - Choi, G. Y.; Kim, S.; Ulman, A. (Langmuir, 1997)

(untitled) - Kim, S.; Choi, G. Y.; Ulman, A.; Fleischer, C. (Langmuir, 1997)

(untitled) - Sun, Y.; Akhremitchev, B.; Walker, G. C. (Langmuir, 2004)

(untitled) - Gillies, G.; Prestidge, C. A.; Attard, P. (Langmuir, 2002)

(untitled) - Vakarelski, I. U.; Toritani, A.; Nakayama, M.; Higashitani, K. (Langmuir, 2001)

(untitled) - Brun, C.; Delobelle, P.; Fromm, M.; Berger, F.; Chambaudet, A.; Jaffiol, F. (Mater. Sci. Eng., A, 2001)

(untitled) - Ashby, M. F. (Acta Metall., 1989)

(untitled) - Maivald, P.; Butt, H. J.; Gould, S. A. C.; Prater, C. B.; Drake, B.; Gurley, J. A.; Elings, V. B.; Hansma, P. K. (Nanotechnology, 1991)

(untitled) - Üzüm, C.; Hellwig, J.; Madaboosi, N.; Volodkin, D.; von Klitzing, R. (Beilstein J. Nanotechnol., 2012)

(untitled) - Braithwaite, G. J. C.; Luckhan, P. F. (J. Colloid Interface Sci., 1999)

(untitled) - Cannara, R. J.; Brukman, M. J.; Carpick, R. W. (Rev. Sci. Instrum., 2005)

(untitled) - Edwards, S. A.; Ducker, W. A.; Sader, J. E. (J. Appl. Phys., 2008)

(untitled) - Deuschle, J.; Enders, S.; Arzt, E. (J. Mater. Res., 2007)

(untitled) - Lin, D. C.; Dimitriadis, E. K.; Horkay, F. (J. Biomech. Eng., 2007)

(untitled) - Cabibbo, M.; Ricci, P.; Cecchini, R.; Chudoba, T.; Rymuza, Z.; Sullivan, J.; Dub, S.; Cohen, S. (Micron, 2012)

(untitled) - Notbohm, J.; Poon, B.; Ravichandran, G. (J. Mater. Res., 2012)

(untitled) - Zhang, Y.-R.; Bai, S.-L.; Yang, D.-Y.; Zhang, Z.; Kao-Walter, S. (J. Polym. Sci., Part B: Polym. Phys., 2008)

(untitled) - Dokukin, M. E.; Sokolov, I. (Macromolecules, 2012)

(untitled) - Vanlandingham, M. R.; McKnight, S. H.; Palmese, G. R.; Elings, J. R.; Huang, X.; Bogetti, T. A.; Eduljee, R. F.; Gillespie, J. W., Jr (J. Adhes., 1997)

Encyclopedia of Surface and Colloid Science - Sader, J. (Calibration of Atomic Force Microscope Cantilevers, 2002)

(untitled) - Takagi, S. (J. Mater. Res., 2012)

(untitled) - Chiu, Y. L.; Ngan, A. H. W. (Acta Mater., 2002)

(untitled) - Bull, S. J. (Z. Metallkd., 2002)

(untitled) - Villarrubia, J. S. (J. Res. Natl. Inst. Stand. Technol., 1997)

(untitled) - Markiewicz, P.; Cohen, S. R.; Efimov, A.; Ovchinnikov, D. V.; Bukharaev, A. A. (Probe Microsc., 1999)

(untitled) - Clifford, C. A.; Seah, M. P. (Appl. Surf. Sci., 2005)

(untitled) - Young, T. J.; Monclus, M. A.; Burnett, T. L.; Broughton, W. R.; Ogin, S. L.; Smith, P. A. (Meas. Sci. Technol., 2011)

(untitled) - Griepentrog, M.; Krämer, G.; Capella, B. (Polym. Test., 2013)

(untitled) - Hayes, S. A.; Goruppa, A. A.; Jones, F. R. (J. Mater. Res., 2004)

(untitled) - Rutland, M. W.; Tyrrell, J. W. G.; Attard, P. (J. Adhes. Sci. Technol., 2004)

(untitled) - Pratt, J. R.; Shaw, G. A.; Kumanchik, L.; Burnham, N. A. (J. Appl. Phys., 2010)